Mythic frontiers : remembering, forgetting, and profiting with cultural heritage tourism - Maher, Daniel R. (Cultural heritage studies, 2017)
This work illustrates how aggrandized versions of the past have been used to turn a profit. Examining the imagined frontier town of Fort Smith, Arkansas, Daniel Maher warns that disconnecting cultural heritage tourism from history minimizes the devastating consequences of imperialism, racism, and sexism and relegitimizes the privilege bestowed upon white men.